2015
DOI: 10.1371/journal.pone.0121564
|View full text |Cite
|
Sign up to set email alerts
|

On the Automaticity of the Evaluative Priming Effect in the Valent/Non-Valent Categorization Task

Abstract: It has previously been argued (a) that automatic evaluative stimulus processing is critically dependent upon feature-specific attention allocation and (b) that evaluative priming effects can arise in the absence of dimensional overlap between the prime set and the response set. In line with both claims, research conducted at our lab revealed that the evaluative priming effect replicates in the valent/non-valent categorization task. This research was criticized, however, because non-automatic, strategic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Similarly, Everaert, Spruyt, Rossi, De Houwer, and Pourtois (2014) showed that EEG correlates of early orienting responses towards rare, emotional stimuli were larger when the evaluative stimulus dimension was selectively attended to as compared to when a non-emotional stimulus dimension was selectively attended to. In sum, FSAA seems to modulate the very process of automatic 1 There is currently an intense debate concerning the question whether effects in the standard evaluative priming paradigm can arise in the absence of overlap between the response set and the prime set (see Becker;& Spruyt, in press;Klauer, Becker, & Spruyt, in press;Werner & Rothermund, 2013;Rothermund & Werner, 2014;Spruyt, 2014;Spruyt & Tibboel, 2015). Crucially, this discussion concerns the mechanism(s) that translate the outcome of the prime-evaluation process into an observable effect (e.g., response compatibility, encoding facilitation, etc.…”
mentioning
confidence: 99%
“…Similarly, Everaert, Spruyt, Rossi, De Houwer, and Pourtois (2014) showed that EEG correlates of early orienting responses towards rare, emotional stimuli were larger when the evaluative stimulus dimension was selectively attended to as compared to when a non-emotional stimulus dimension was selectively attended to. In sum, FSAA seems to modulate the very process of automatic 1 There is currently an intense debate concerning the question whether effects in the standard evaluative priming paradigm can arise in the absence of overlap between the response set and the prime set (see Becker;& Spruyt, in press;Klauer, Becker, & Spruyt, in press;Werner & Rothermund, 2013;Rothermund & Werner, 2014;Spruyt, 2014;Spruyt & Tibboel, 2015). Crucially, this discussion concerns the mechanism(s) that translate the outcome of the prime-evaluation process into an observable effect (e.g., response compatibility, encoding facilitation, etc.…”
mentioning
confidence: 99%
“…This is the automatic, i.e., unintended, passive and unconscious, influence of stereotype priming on behavior, according to these authors. These and similar effects elicited by priming in the context of the automaticity (vs. control) of social constructs, as well as of social evaluations (see Section 3.5.2 below), have been abundantly reported (e.g., Aarts et al, 2005 Abbate et al, 2013;Blair & Banaji, 1996;Spruyt & Tibboel, 2015;Steele & Ambadi, 2006). …”
Section: Automatic Vs Controlled Processingmentioning
confidence: 74%
“…We have recently summarized empirical work, however, suggesting that the contribution of linguistic factors is probably quite small (Klauer et al, in press). In sum, more research is needed to further examine the extent to which evaluative information can impact early encoding processes, preferably using a diverse set of paradigms that (Gast et al, 2014;Spruyt, 2014;Spruyt and Tibboel, 2015;Werner & Rothermund, 2013; also see online supplement).…”
Section: Discussionmentioning
confidence: 99%
“…As has also been argued by Werner and Rothermund (2013), a combination of selective attention and dimension-relevant response compatibilities might be necessary to produce the respective semantic priming effects. However, the debate on this question, which is also at the heart of this article, persists Spruyt, 2014;Spruyt and Tibboel, 2015). Spruyt, De Houwer, & Hermans (2009) original study Procedure As described above, Spruyt and colleagues (2009, Exp.…”
mentioning
confidence: 96%